Active and Passive Earth Pressure Calculation Method for Double-Row Piles considering the Nonlinear Pile Deformation. (26th April 2022) - Zhou, Yijun; Chen, Yulong
Abstract : The double-row pile supporting structure has been widely used in foundation pit excavations. When analyzing the effect of earth pressure on the pile structure, previous research only considered the double-row piles as the rigid body and the pile-soil interaction has not been examined. In this study, a theoretical model was developed based on Duncan-Chang's hyperbolic theory to calculate earth pressures in the active and passive zones of the double-row pile supporting structure. The model considered the nonlinear effect of the pile deformation on the active and passive earth pressures. The macroscopic pile-soil interaction was converted into a microscopic stress-strain relationship at a certain point in the soil body, reflecting the nonlinear effect of pile deformation on earth pressure. Numerical simulation and large-scale field tests have been conducted to verify the proposed model. The results show that the average values of the parameters obtained by numerical simulation are a ¯ = 0.38, b ¯ = − 0.253 for the active zone and a ¯ = 0.00612, b ¯ = − 0.729 for the passive zone. Based on the values of a ¯ and b ¯, the predicted active and passive earth pressures stemming from the developed model agreed well with those obtained from field tests. The developed model in this study can be used to predict the distribution of active and passive earth pressures for double-row pile supporting structures.